Pharmacological Activity of Elephantopus mollis Kunth: A Review - Rusdi, Mesa Sukmadani; Efendi, M. Rifqi (Journal of Basic and Applied Pharmacology, 2021)
Elephantopus mollis Kunth., belongs to the family Asteraceae is a herbaceous perennial that originated from tropical America and was widely introduced to high rainfall tropical Africa, Asia and the Pacific. The whole plant and parts of this plant have been traditionally used and extensively studied for the treatment of various diseases, especially as cytotoxic agents. Other pharmacological activities such as anti-inflammatory, antioxidant, anti-leishmaniasis, antiprotozoal, antimicrobial, antidiabetic, bone stimulating regeneration and hepatoprotection activity have been reported in various research articles. This review intends to provide comprehensive investigations and findings of pharmacological activity from Elephantopus mollis Kunth., as well as the traditional uses, phytochemical constituents, and isolated compounds from E. mollis Kunth.